Performance trends in large 10-km road running races in the United States - Cushman, D. M.; Markert, M.; Rho, M. (The Journal of Strength and Conditioning Research, 2014)
Our study examines the current trends of runners participating in 10-km road races in the United States. Finish times and ages of all runners participating in 10 of the largest 10-km running races in the United States between 2002-2005 and 2011 were recorded. Linear regression analysis was performed to examine the trends for age, sex, and finishing time for all participants completing the course in <1 hour. A total of 408,296 runners were analyzed. There was a significant annual decrease in the ratio of men to women finishers (p < 0.001, r2 = 0.976). The average finishing time of the top 10 (men, p < 0.05), 100 (men and women, p < 0.05), and 1,000 (men and women, p < 0.01) significantly decreased annually. The total number of subhour finishers increased annually across all races (194 men per year, r2 = 0.584, p = 0.045; 161 women per year, r2 = 0.779, p = 0.008), whereas the percentage of overall finishers completing the course in less than an hour significantly declined for men and women (p < 0.003). There was a significant trend toward younger men in all top groups except for the single fastest runner (p < 0.017). Our study demonstrates that for large 10-km U.S. races: the top men and women seem to be getting faster; there are more subhour finishers, with increasingly more women accomplishing this feat compared with men; an increasingly lower percentage of overall finishers is finishing in <1 hour; and the fastest men are also increasingly younger.